Designer electrode interfaces simultaneously comprising three different metal nanoparticle (Au, Ag, Pd)/carbon microsphere/carbon nanotube composites: progress towards combinatorial electrochemistry. - Dai, X; Wildgoose, G; Compton, R (2006)
In this report gold, silver and palladium metal nanoparticles are separately supported on glassy carbon microspheres (GCM) using bulk electroless deposition techniques to produce three different materials labelled as GCM-Au, GCM-Ag and GCM-Pd respectively. These three materials are then combined together into a composite film on a glassy carbon (GC) electrode surface using multiwalled carbon nanotubes (MWCNTs). The MWCNTs serve to not only mechanically support this composite film as a "binder" but they also help to "wire up" each modified GCM to the underlying substrate. The intelligently designed structure of this electrode interface allows this single modified electrode to simultaneously behave as if it were a macrodisc electrode constructed of gold, silver or palladium, whilst using only a fraction of the equivalent amount of these precious metals. Furthermore this unique structure allows the possibility of combinatorial electrochemistry to be realised using a relatively facile electrode construction which avoids the problems of alloy formation, co-deposition and the formation of bimetallic species. For instance a mixture of several different analytes, which can each only be detected on a different specific substrate, can simultaneously be determined using one electrode in a single voltammetric experiment! Alternatively a substrate could undergo electrocatalytic reactions on one substrate, whilst the products, and hence the progress of this reaction, can be studied at a different substrate simultaneously at the same electrode surface. Proof-of-concept examples are presented herein and the designer electrode interface is shown to produce analytical responses to model target analytes such as hydrazine, bromide and thallium(I) ions that are comparable, if not better, than those obtained at metal macrodisc electrodes and even at other state-of-the-art nanoparticle modified electrodes.